(untitled) (Orinoquia, 2019)
With the aim of reproducing the vizcaina Curimata mivartii, two-year-old specimens (n = 54), kept in ponds on land (0.1 fish/m2) were induced with carp pituitary extract (EPC) (Argent, USA) at a doses of 6 mg/Kg of weight for females in two applications (10% and 90% with 12 hours between applications), while males were induced with 4.8 mg / Kg EPC in a single dose. Before the hormonal induction, each female underwent an ovarian biopsy to verify the oocytes maturation stage. The oocyte sample was treated with Serra solution (Chemi, Colombia) and after three minutes, with the help of a light stereoscope (Leica, EZ4 W, Germany) in 4x objective, the position of the germinal vesicle was determined (central, migrating, peripheral, breakdown). The analysis of the ovarian biopsy showed that the females were in final maturation. Induced males were found in the spermiation phase; which at light abdominal pressure released seminal fluid. The ovulation index, fecundity (absolute and relative), oocyte diameter and seminal volume were estimated. The percentage of fertility was estimated at four hours after hatching (hah); and the hatching percentage was estimated at 10 hah. The females ovulated between 5 and 6 hours (28±1.0°C) and immediately the eggs were obtained by extrusion, as well as the semen. The absolute fecundity was 178331.6±28773.7 oocytes/female and the relative 137.7±19.6 g oocytes/Kg of female. The diameter of the newly spawned oocytes was 687.2±42.8 μm. Fertility was 90.7±1.4% and hatching 85.3±1.5%. The results allow to conclude that EPC at dosage of 6mg/Kg of weight is a good inducer of the vizcaína reproduction, which high ovulation index and high rates of fertility and hatching.